Pica is prevalent and strongly associated with iron deficiency among Hispanic pregnant women living in the United States. (1st January 2018) - Roy, Aditi; Fuentes-Afflick, Elena; Fernald, Lia C.H.; Young, Sera L.
Abstract: Introduction: Anecdotal evidence suggests that pica occurs among Hispanic women in the United States, especially during pregnancy. However, the prevalence and socio-demographic and biological factors associated with pica in this population have not been adequately identified. Methods: Trained, bilingual study personnel conducted structured interviews at public health clinics in Salinas Valley, California with 187 pregnant Hispanic women in their 2nd or 3rd trimesters of pregnancy. Hemoglobin was measured using Hemocue; concentrations of transferrin receptor (TfR) and alpha-1 acid glycoprotein (AGP) were measured in dried blood spots. Multivariable stepwise regression analyses were conducted with pica during pregnancy as the dependent variable and individual- and family-level factors as independent variables to identify significant associations. Additionally, multivariable models were built to explore the associations between pica and iron status (iron deficiency and anemia). Results: Half of all participants (51.3%) had ever engaged in pica, and 37.6% had done so during the current pregnancy. Pica substances included large quantities of ice, frost, raw starches, and various earthen items. Pica during the current pregnancy was significantly associated with higher TfR concentrations [OR: 1.29; 95% CI: 1.11, 1.51] indicative of low iron stores and greater food insecurity [OR: 1.20, 95% CI: 1.03, 1.40]. Women who engaged in pica during the current pregnancy were more likely to be iron deficient [adjusted OR: 2.58; 95% CI: 1.19, 5.60], but not anemic [adjusted OR: 1.40; 0.60, 3.23]. Conclusions: Among pregnant Hispanic women, pica was prevalent and strongly associated with iron deficiency and food insecurity. Clinicians should screen for pica during pregnancy in Hispanic populations, and future studies should elucidate the underlying etiology and consequences of engaging in pica during pregnancy.